Research on Consumer Purchasing Channel Choice Based on Product Tolerance: The Mediating Role of Rationalization - Chen, Jinsong; Wu, Yumin; Jiang, Xue (Frontiers in Psychology, 2022)
Consumers have subjective psychological expectations about the quality and brand of products before purchasing. There is a certain tolerance for the products that do not meet the psychological expectations. The discomfort caused by tolerance can smoothly carry out through "reasonable" self-comfort and explanation mechanisms. Based on the theory of rationalization defense mechanism, a 2X2 purchase channel matrix of online or offline purchase, online consultation or offline experience was constructed to explore the influence of consumers' tolerance of product quality and brand on their purchase channel choice. The results show that :(1) Consumer tolerance of products positively influences consumers' online purchasing behavior；(2) in the rationalization of defense mechanism mediating role, sweet lemon psychological, tolerance to consumer product quality and brand, select online consulting online purchase online and offline experience have a positive promoting effect; (3) sour grapes tolerate product quality and brand for consumers choose online consulting online purchase online and offline experience without intermediary role.